Sumando Custom as a Coastal Ethnic Hybrid Identity in Sibolga City, North Sumatra Province - Indah Wulandari Pulungan; Nopriyasman Nopriyasman; Gusti Asnan (Eduvest - Journal of Universal Studies, 2024)
This research was conducted to explain the background to the formation of the Sumando custom, the forms of the Sumando custom, and the meaning of the Sumando custom as a hybrid ethnic identity in Pesisir Sibolga. The theory used to analyze the object of this research is hybridity theory and deconstruction theory. Research on "Sumando Custom as a Coastal Ethnic Hybrid Identity in Sibolga City" taking the perspective of Cultural Studies was carried out with qualitative research based on descriptive data. The hybrid identity in the Sumando custom owned by the Pesisir ethnic in Sibolga is a phenomenon of changes in cultural identity experienced by several ethnic groups in Sibolga City. The Sumando tradition is a new identity owned by the Pesisir Sibolga ethnic group. The assimilation that exists between the Pesisir, Batak and Minangkabau people creates a new custom and culture that is suitable to be used as a shared guide in living in society on the Sibolga Coast in accordance with Islamic law.